The Influence Of Leadership Behavior, Motivation, Compensation, And Work Discipline On Employee Performance At PT. Holyland Food Indonesia - Nopianto, Nopianto; Susanti, Neri; Fitriano, Yun (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
Efforts to assess performance become important with the knowledge of the correct performance measurements. Performance is measured based on quality, quantity, timeliness, effectiveness, independence, and commitment. The purpose of this research is to determine the influence of leadership behavior, motivation, compensation, and work discipline on employee performance at PT. Holyland Food Indonesia. The sample in this study consists of 98 permanent employees at PT. Holyland Food Indonesia. Data collection is done using questionnaires, and the analysis methods used are multiple linear regression, determination test, and hypothesis test. The regression analysis results show Y = 0.239 + 0.171X1 + 0.379 X2 + 0.226X3 + 0.245X4. Leadership behavior has a positive and significant influence on performance in employees at PT. Holyland Food Indonesia with a significant value of 0.027, which is less than 0.05. This indicates that as leadership behavior increases, the performance of employees at PT. Holyland Food Indonesia will also increase. Motivation shows a positive and significant influence on performance in employees at PT. Holyland Food Indonesia with a significant value of 0.000, which is less than 0.05. This indicates that as motivation increases, the performance of employees at PT. Holyland Food Indonesia will also increase. Compensation shows a positive and significant influence on performance in employees at PT. Holyland Food Indonesia with a significant value of 0.001, which is less than 0.05. This indicates that as compensation increases, the performance of employees at PT. Holyland Food Indonesia will also increase. Work discipline has a positive and significant influence on performance in employees at PT. Holyland Food Indonesia with a significant value of 0.003, which is less than 0.05. This indicates that as work discipline increases, the performance of employees at PT. Holyland Food Indonesia will also increase.